Palliative Care in the Time of COVID-19 - Mercadante, Sebastiano (J Pain Symptom Manage, 2020)
After COVID-19 crisis in Italy, serious restrictions have been introduced for relatives, with limitations or prohibitions on hospital visits. To partially overcome these issues “WhatsApp” has been adopted to get family members to participate in clinical rounds. Family members of patients admitted to the acute palliative care unit and hospice were screened for a period of two weeks. Four formal questions were posed: 1) Are you happy to virtually attend the clinical round? 2) Are you happy with the information gained in this occasion? 3) Do you think that your loved one was happy to see you during the clinical rounds? 4) This technology may substitute your presence during the clinical rounds? The scores were 0 = no, 1 = a little bit, 2 = much, 3 = very much. Relatives were free to comment about these points. Sixteen of 25 screened family members were interviewed. Most family members had a good impression, providing scores of 2 or 3 for the first three items. However, the real presence bedside (forth question) was considered irreplaceable. They perceived that their loved one, when admitted to hospice, had to say good-bye before dying.